2017
DOI: 10.3389/fimmu.2017.00048
|View full text |Cite
|
Sign up to set email alerts
|

Cell Intrinsic Galectin-3 Attenuates Neutrophil ROS-Dependent Killing of Candida by Modulating CR3 Downstream Syk Activation

Abstract: Invasive candidiasis is a leading cause of nosocomial bloodstream infection. Neutrophils are the important effector cells in host resistance to candidiasis. To investigate the modulation of neutrophil fungicidal function will advance our knowledge on the control of candidiasis. While recombinant galectin-3 enhances neutrophil phagocytosis of Candida, we found that intracellular galectin-3 downregulates neutrophil fungicidal functions. Co-immunoprecipitation and immunofluorescence staining reveal that cytosolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 51 publications
3
29
1
Order By: Relevance
“…While the minimal ROS activation at the early time points cannot be attributed to modulation of gene expression by F. alocis, generation of ROS at later time points may be inhibited by the expression of a member of the galectin family of carbohydrate-binding proteins, galectin-3. The increased expression of galectin-3 has already been associated with inhibition of ROS production when human neutrophils were challenged with Candida albicans (48). In our dataset, both the FPKM expression as well as the qPCR validation show a time-dependent increase in galectin-3 mRNA expression ( Figures 1E,F), and when tested by western blot, F. alocis induced a time dependent increase in galectin-3 protein expression (data not shown).…”
Section: F Alocis Affects Neutrophil Functional and Biochemical Procsupporting
confidence: 60%
See 1 more Smart Citation
“…While the minimal ROS activation at the early time points cannot be attributed to modulation of gene expression by F. alocis, generation of ROS at later time points may be inhibited by the expression of a member of the galectin family of carbohydrate-binding proteins, galectin-3. The increased expression of galectin-3 has already been associated with inhibition of ROS production when human neutrophils were challenged with Candida albicans (48). In our dataset, both the FPKM expression as well as the qPCR validation show a time-dependent increase in galectin-3 mRNA expression ( Figures 1E,F), and when tested by western blot, F. alocis induced a time dependent increase in galectin-3 protein expression (data not shown).…”
Section: F Alocis Affects Neutrophil Functional and Biochemical Procsupporting
confidence: 60%
“…Although the minimal ROS induced by F. alocischallenged neutrophils was monitored between 1 and 90 min and the significant decrease in p47phox gene expression was observed at 6 h post-infection, these pathogen-induced changes in the transcript levels could leave neutrophils defective in mounting an appropriate respiratory burst response. Furthermore, cytosolic galectin-3 acts as a negative regulator of ROS production in both human and mouse neutrophils by modulating complement receptor 3 signaling pathway during C. albicans infections (48). Our results show a time-dependent increase in galectin-3 gene expression which could be one of the strategies used by F. alocis to inhibit ROS production.…”
Section: Discussionmentioning
confidence: 61%
“…However, galectin-3-deficient neutrophils had a higher level of ROS than the control strain after exposure to C. albicans. This effect is mediated via a physical interaction between galectin-3 with the CR3 downstream component Syk (Wu et al, 2017). Interestingly, additional receptors are suspected to recognize β-glucan as PBMCs have been identified to produce IL-1Ra in response to C. albicans hyphae in a Dectin-1-and CR3-independent manner (Smeekens et al, 2015).…”
Section: Recognition Of Glucanmentioning
confidence: 99%
“…It has also been suggested that galectin-3 can have a dual role in the regulation of neutrophil function, depending on its cellular location. While recombinant galectin-3 was shown to enhance neutrophil phagocytosis of C. albicans , it was also found that intracellular galectin-3 can downregulate neutrophil fungicidal activities by physically interacting with Syk and therefore reducing ROS-dependent killing of C. albicans [48]. …”
Section: Additional Mannose-binding Lectinsmentioning
confidence: 99%